Cricket and yellow mealworm powders promote higher bioaccessible fractions of mineral elements in functional bread. (December 2022) - Mihaly Cozmuta, A.; Nicula, C.; Peter, A.; Mihaly Cozmuta, L.; Nartea, A.; Kuhalskaya, A.; Pacetti, D.; Silvi, S.; Fiorini, D.; Pruteanu, L.
Graphical abstract: Highlights: Cricket (CPB-10%), mealworm (YMPB-10%) and white (WFB-100%) breads are assessed. Na, K, Ca, Mg, P, Fe, Zn, Mn, Li have maximum bioaccessibility in insect-breads. Mg in CPB-10% has the highest (97.19%) and Cu the lowest (22.24%) bioaccessibility. Mn in YMPB-10% has the highest (97.22%) and Cu the lowest (4.96%) bioaccessibility. Cu has higher bioaccessibility in WFB-100% (46.24%) than in CPB-10% and YMPB-10%. Abstract: The application of cricket and yellow mealworm powders to improve the mineral bioaccessibility of bread was investigated. Breads enriched with 10% cricket (CPB-10%) and 10% yellow mealworm (YMPB-10%) powders showed a 1.5-, 2.95-, and 1.22-fold increase in proteins, total lipids, and fibers, respectively, compared to the reference white wheat bread (WFB-100%). Compared to reference bread, a significant increase in the essential amino acids valine (9.72%) and tyrosine (1.86%) contents was observed in the CPB-10% and YMPB-10%. The MUFAs account for 35.22% in CPB-10%, 30.77% in YMPB-10%, and 32.34% in WFB-100%. In vitro digestion experiments showed a higher bioaccessibility of Na, K, Ca, Mg, P, Fe, Zn, Mn, and Li from insect bread than from white bread. Only Cu was more bioaccessible from WFB-100% than from insect bread. The results shed light on the possible contribution of insect bread consumption to mitigate deficiencies in several important macro- and microelements.